A Prospective Cohort Study of Gestational Weight Gain, Postpartum Weight Retention, and Maternal Health in Vietnam - Ha, Vo Van Anh (Curtin University, 2020)
The studies presented in this thesis are the first published investigations of physical activity on maternal weight changes, postpartum low back pain and on periconceptional folic acid supplementation in Vietnam. Prenatal and postnatal physical activity are protective factors for excessive gestational weight gain, postpartum weight retention, and low back pain. Folic acid supplementation in the periconceptional period is recommended to prevent neural tube defects, but the rate of correct use in Vietnam is too low.